2018
DOI: 10.1002/jnr.24235
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the trajectory of the amygdalothalamic tract in the human brain

Abstract: Although the thalamus is not considered primarily as a limbic structure, abundant evidence indicates the essential role of the thalamus as a modulator of limbic functions indirectly through the amygdala. The amygdala is a central component of the limbic system and serves an essential role in modulating the core processes including the memory, decision-making, and emotional reactions. The amygdalothalamic pathway is the largest direct amygdalo-diencephalic connection in the primates including the human brain. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Also, our results show that the fiber connection in the amygdala as parts of the fornix that extend anterior to the perforant pathway. This result is consistent with the recent report which described the amygdalothalamic tract that travels with the fornix (Kamali et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Also, our results show that the fiber connection in the amygdala as parts of the fornix that extend anterior to the perforant pathway. This result is consistent with the recent report which described the amygdalothalamic tract that travels with the fornix (Kamali et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Kamali and colleagues described a robust methodology to track the ATT in a healthy cohort based on a high resolution DTI dataset. 18 We translated the methodology to our MS cohort and demonstrated that it is also feasible with a relatively standard acquisition protocol used in clinical trials involving MS patients. Functionally this tract was implicated in the rapid shifting of attention to emotional stimuli, 24 assessment in purposefulness and social appropriateness of emotional stimuli, and social cognition.…”
Section: Discussionmentioning
confidence: 99%
“…17 It then projects inferolaterally, travels adjacent to forniceal fibers and reaches the amygdala. 18 For deterministic tractography methodology, we used brute force, ROI-based, the fiber assignment with continuous tractography (FACT) algorithm 19,20 (DTI Studio, Johns Hopkins University, Baltimore, MD) and our ROI based approach illustrated and described in figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The equivalent fiber connectivity of all these pathways has been documented by dissection studies in primates. Some of these fiber tracts include the amygdalofugal tract (AFT), amygdalothalamic tract (ATT), stria terminalis (ST), dorsal thalamo-hypothalamic tract (DTH), cerebello-hypothalamic tracts, and the parieto-occipito-hypothalamic tract (POHT) (Kamali et al 2015 ; Kamali et al 2016 ; Kamali et al 2018a , b ; Kamali et al 2018a , b ; Kamali et al 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…1 ) (Yamada et al 1998 ; Haines 2007 ). The hypothalamic nuclei, specifically the mammillary bodies, are involved in many limbic circuitry and directly or indirectly connected to the amygdala, hippocampus, and thalamus (Yamada et al 1998 ; Kamali et al 2018a , b ). The mammillothalamic is a projection bundle that arises from the mammillary bodies, projects dorsally, and cranially, toward the thalamus.…”
Section: Introductionmentioning
confidence: 99%